2005
DOI: 10.1592/phco.2005.25.6.823
|View full text |Cite
|
Sign up to set email alerts
|

Selecting an Equation to Estimate Glomerular Filtration Rate for Use in Renal Dosage Adjustment of Drugs in Electronic Patient Record Systems

Abstract: Electronic patient record databases may not contain a nominal variable database field for black or non-black status, which is required by the MDRD equations. The Cockcroft-Gault equation that used corrected weight and BSA adjustment performed about as well as the abbreviated MDRD equation and can be programmed into electronic patient records. Given the small number of black patients included in this study, further study in this patient population is recommended before applying this Cockcroft-Gault variant to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Our finding of 11 to 29% discordance between the MDRD Study and CG equations overall and in subgroups is consistent with some previous studies which have showed discordance rates between approximately 20 to 40% between the equations 2024. Possible explanations for the variation in reported discordance rates may be related to true differences in accuracy of equations among study populations included in the different reports or to variations in the methods utilized to estimate kidney function (e.g.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding of 11 to 29% discordance between the MDRD Study and CG equations overall and in subgroups is consistent with some previous studies which have showed discordance rates between approximately 20 to 40% between the equations 2024. Possible explanations for the variation in reported discordance rates may be related to true differences in accuracy of equations among study populations included in the different reports or to variations in the methods utilized to estimate kidney function (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies have compared drug dosing recommendations based on CG equation to those based on the MDRD Study equation2024, but none have compared these recommendations to those based on measured GFR in a large, clinically diverse population. The two objectives of this study were: 1) to compare kidney function categories as defined by the FDA Guidance for Industry using kidney function estimates based on the MDRD Study equation and CG equation using actual and ideal body weight to measured GFR and, 2) to compare differences in hypothetical recommended dosing of 15 medications that are cleared by the kidneys among 5,504 patients from 6 research and 4 clinical populations with diverse clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] The MDRD approach is particularly attractive to hospital clinical laboratory programs, as it allows for the automatic calculation and reporting of the GFR by an institution's clinical laboratory software without regard to patient body weight. The National Kidney Disease Education Program (NKDEP) embraces this concept and recommends concomitant reporting of the estimated GFR with each SCr value to improve the detection of renal dysfunction among hospitalized patients.…”
mentioning
confidence: 99%
“…The results of this study may help optimize drug information services particularly when they are computerbased because in different areas [18], including dose adjustment for renal insufficiency [2,19,20], computerized clinical decision support systems successfully prevented overdosing. However, such systems are not forcefully used in routine care unless they are integrated into a CPOE [21].…”
Section: Discussionmentioning
confidence: 96%